2022
DOI: 10.3390/ani12030386
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heat Stress and Vitamin and Micro-Mineral Supplementation on Some Mineral Digestibility and Electrolyte Balance of Pigs

Abstract: Heat stress (HS) can have detrimental effects on intestinal integrity and can jeopardize the digestibility performance in pigs. With prolonged exposure to heat, some thermoregulatory processes in pigs are potential causes for electrolyte imbalance. The adverse effects of HS on mineral digestibility and electrolyte balance are not widely studied and information on its abatement through vitamin and micro-mineral supplementation in combinations above the recommended level in pigs is limited. The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Supplementing pigs with vitamin A during heat stress conditions has been shown to have beneficial effects on their performance and health. Vitamin A supplementation can improve mineral digestibility, correct electrolyte imbalances, and enhance overall resilience to heat stress [75]. In addition to the challenges posed by diseases in swine, the impact of heat-induced stress on pigs further underscores the multifaceted concerns within the swine industry.…”
Section: Vitamin Amentioning
confidence: 99%
See 2 more Smart Citations
“…Supplementing pigs with vitamin A during heat stress conditions has been shown to have beneficial effects on their performance and health. Vitamin A supplementation can improve mineral digestibility, correct electrolyte imbalances, and enhance overall resilience to heat stress [75]. In addition to the challenges posed by diseases in swine, the impact of heat-induced stress on pigs further underscores the multifaceted concerns within the swine industry.…”
Section: Vitamin Amentioning
confidence: 99%
“…They found that while it did not reduce oxidative stress during cyclic heat stress, it did alleviate respiratory alkalosis, suggesting its potential as a summer ration supplement [166]. Additionally, a combination of vitamin E and selenium at elevated levels above recommendations has been shown to improve mineral digestibility, including calcium, selenium, and zinc, despite heat stress exposure [75]. Selenium, in the form of selenocysteine (SeCys) within selenoproteins like selenoprotein P (SelP) and extracellular glutathione peroxidase (GPx3), acts as a vital constituent, shielding cells against oxidative stress by counteracting reactive oxygen species (ROS) [167,168].…”
Section: Vitamin Ementioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has demonstrated that combining micronutrients (Zn, Se, Vitamin E, and Vitamin C) has improved animals' resistance to the harmful effects of heat stress. Animal performance under HS may be improved by the substances' capacity to prevent cell damage and enhance intestinal integrity and renal function [10]. The metabolic and physiological processes of several species of animals can also be improved by adding vitamins and minerals [11,12].…”
Section: Introductionmentioning
confidence: 99%